Stari Vinogradi - Bronze Age necropolis in Ostojićevo (Kikinda) - Milašinović Lidija; Kapuran Aleksandar; Bulatović Aleksandar (Starinar)
The Bronze Age Maros culture necropolis in Ostojićevo in the northern Vojvodina region was excavated during the 1980s and the beginning of the 1990s, yet remains incompletely published. Its importance for Serbian archaeology is the fact that it represents one of the two necropolises from the transition between the Early and the Middle Bronze Age in the territory of Serbia and one of a total of six necropolises of the Maros culture. In terms of material culture recorded in graves, it is not as rich as the neighbouring Mokrin necropolis, yet displays a higher degree of different cultural influences, which can be particularly observed during the later phases of the Maros culture. This article represents the selection of burial contexts, primarily those that are dated, and certain graves that display the aforementioned cultural influences. The article likewise presents the methodology in which the necropolis will be published as a monographic edition, by the authors of this paper.